2004
DOI: 10.1097/01.ogx.0000137612.87012.66
|View full text |Cite
|
Sign up to set email alerts
|

Tools for Post LEEP Surveillance

Abstract: After completion of this article, the reader should be able to list the various tools that can be used for the surveillance of patients after treatment for CIN, to compare the advantages and disadvantages of each surveillance method, and summarize methods to improve compliance with follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 56 publications
0
5
0
1
Order By: Relevance
“…In recent years, several studies have shown that HPV DNA testing is a significant predictor of residual/recurrent disease 20–26 . In a review of 11 studies, sensitivity of HPV DNA testing in detecting residual/recurrent disease reached 100% in four studies, whereas the specificity of the test ranged from 44% to 95%.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, several studies have shown that HPV DNA testing is a significant predictor of residual/recurrent disease 20–26 . In a review of 11 studies, sensitivity of HPV DNA testing in detecting residual/recurrent disease reached 100% in four studies, whereas the specificity of the test ranged from 44% to 95%.…”
Section: Discussionmentioning
confidence: 99%
“…Although follow-up after conization and early detection of treatment failure are important, till date, no standardized follow-up protocol has been developed. Margin involvement, age, menopausal status, human papillomavirus (HPV) persistence and cytological grade are reportedly risk factors for CIN persistence or recurrence after conization [ 6 , 8 , 9 ]. Although the resection margin during conization is considered to be the most important predictor of recurrent disease in patients who undergo cervical conization [ 6 ], several studies have reported that CIN persistence or recurrence is independent of margin involvement [ 8 - 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…What is not clear is the value that colposcopy would add over cytology alone for follow-up given the additional anxiety to patients and increased treatment rates. In face of the increasing body of literature, which suggests high anxiety rates and default from appointments when colposcopy was involved, it is important that these women at high risk for recurrent CIN and invasive disease be offered follow-up strategies, which increase compliance and decrease stress [9,10].…”
Section: Discussionmentioning
confidence: 99%